Social Media and Social Movement - Baihaqi, Rafi (PCD Journal, 2025)
This study analyses the strategies of the Orang Tua Bergerak movement in advocating against the alleged wrongful arrest in the Gedongkuning klitih case of 2022 by employing both digital (online) and direct (offline) methods. Using a qualitative approach and content analysis, this study identifies the strategic and communicative practices developed by the movement in collaboration with cross-movement actors. The findings reveal three key points. First, Orang Tua Bergerak utilised social media platforms, including Instagram, X, and Facebook, to disseminate digital posters, online writings, petitions, and documentary videos. These outputs incorporated injustice framing, aimed at mobilising broader solidarity and drawing attention from diverse movements. Second, the participation of cross-movement networks amplified public sympathy and encouraged the circulation of injustice narratives, which increased societal awareness of the Gedongkuning incident. Third, the heightened public attention was strategically leveraged by Orang Tua Bergerak to conduct direct advocacy at local and national levels, including hearings, discussions, and the Kamisan protest. These findings show how digital mobilisation complements direct action in sustaining advocacy and amplifying social justice campaigns. This study contributes theoretically by conceptualising the transition from digital activism to direct collective action within hybrid social movement frameworks.